Приносът на Иван Богоров към оформянето на българската преса през XIX век - Церан, Лех (Slavica Lodziensia, 2019)
Ivan Bogorov is not only the one of the first Bulgarian journalists, but he is also one of the most important ones. He create several important newspapers and magazines like for example “Bălgarski orel” (bg. “Bulgarian eagle”), “Carigradski vestnik” (bg. “Tsargrad journal”) and “Bălgarski knižici” (bg. “Bulgarian books”). His activity in this field not only created the direction of the development of the Bulgarian press, but also was popularising Bulgarian bookcraft by giving an opportunity of publishing works to authors such as Petko Slavejkov, Jordan Hadžikonstantinov Džinot, Sava Filaretov and Konstantin Miladinov. Thanks to the activists like Ivan Bogorov Bulgarian journalism achieved fast growth and in the period of few years has been aligned with the older and developed presses in Europe, like for example Czech one.